ANALISIS HUKUM ISLAM DAN HUKUM POSITIF TERHADAP FENOMENA MONEY POLITIC - Syapar Alim Siregar (IAIN Padangsidimpuan, 2022)
In every election performance in Indonesia since the beginning of Indonesian independence until the current era, it has always been nodai with dirty election violation practices. One example is the practice of money politics which has always been a shadow for the face of Indonesian democracy. Islam sees the concept of money politics as the same as the concept of risywah or bribery in a broad sense. Where both give rise to tyranny for other groups. There are so many impacts of this money politics practice, one of the most dominant is the increasing number of corruption, collusion, and nepotism in Indonesia. All those things are because of the money that has been spent to buy the people's vote. The way to prevent money politics is to increase the integrity of law enforcement officials in eradicating election violations and providing education to the public on the cause and effect if they receive money politics.